Developing a spinal cord injury rehabilitation service in Madagascar - Rakotonirainy Renaud; Helen N. Locke; Ramaswamy Hariharan; M. Anne Chamberlain; Rory J. O'Connor (Medical Journals Sweden, 2018)
Rehabilitation for people with spinal cord injury in many low- and middle-income countries is not avail-able or is in the early stages of development. However, rehabilitation is recognized as crucial in order to optimize functional recovery and outcomes for patients with spinal cord injury. With an increasing incidence of spinal cord injury, the unmet need for rehabilitation is huge. This report describes the early development of a specialist rehabilitation service for spinal cord injury in Madagascar, one of the poorest countries in the world. The sustained input to an expanding rehabilitation team has led to reductions in avoidable complications. The input of the rehabilitation team has been welcomed by the neurosurgery department, which has recognized fewer delays in patients undergoing surgical treatments. Cost, lack of resources and trained staff, and poor understanding of disability continue to provide challenges. However, the development of the rehabilitation service using low technology, but with a high level of knowledge and systematic management, is a source of considerable pride. This development in Madagascar can be regarded as a model for spinal cord injury rehabilitation in other low-resource settings.